Impact of direct oral anticoagulants on evolution of post-thrombotic syndrome. Issue 207 (November 2021) - Di Pino, Luigi; Francaviglia, Bruno; Frazzetto, Marco; Valenti, Noemi; Capranzano, Piera
Abstract: Background: The effect of direct oral anticoagulants (DOACs) on evolution of a post-thrombotic syndrome (PTS) is unknown. Methods and results: This retrospective study included patients ( n = 98) with a PTS occurring after a proximal deep-vein thrombosis (DVT). The PTS progression was assessed by the Villalta scale change over time from when patients were started on DOACs for the prevention of DVT recurrence according to current guidelines. The PTS evolution was compared between patients with good ( n = 63) vs. poor ( n = 35) DOACs adherence, defined by using a medication possession ratio cut point of 0.80. The mean follow-up was 41.7 ± 17.7 and 27.5 ± 10.5 months in patients with good or poor adherence, respectively. The primary endpoint of PTS improvement (defined when the Villalta score became <5 and/or decreased by ≥30% from baseline) was higher in patients with good vs. poor adherence (66.7% vs. 20%, p < 0.001). None of the patients in the good adherence group experienced at any time of follow-up the co-primary endpoint of PTS worsening (defined as the Villalta score increase ≥30%), which instead occurred in 12 (34.3%) of those with poor adherence ( p < 0.001). All study-defined primary endpoints occurred within 2 years. The mean values of the Villalta partial scores related to the subjective symptoms (patient-rated) and to the potentially reversible physician-rated signs were significantly improved in the good adherence group, while they were unchanged among patients with poor adherence. Conclusions: In this study a good vs. poor DOACs adherence was associated with a more favorable progression of PTS over a long-term follow-up. Larger studies are needed to explore the clinical efficacy of DOACs on PTS manifestations. Highlights: The study shows novel data on anticoagulation treatment of post-thrombotic syndrome. Direct oral anticoagulants favorably impacted on post-thrombotic syndrome course. Direct oral anticoagulants provide a faster improvement of post-thrombotic syndrome. Studies on direct oral anticoagulants effect on post-thrombotic syndrome are needed.